The age of algorithms - Abiteboul, S. (Serge); Dowek, Gilles (Cambridge : Cambridge University Press, 2020)
Algorithms are probably the most sophisticated tools that people have had at their disposal since the beginnings of human history. They have transformed science, industry, society. They upset the concepts of work, property, government, private life, even humanity. Going easily from one extreme to the other, we rejoice that they make life easier for us, but fear that they will enslave us. To get beyond this vision of good vs evil, this book takes a new look at our time, the age of algorithms. Creations of the human spirit, algorithms are what we made them. And they will be what we want them to be: it's up to us to choose the world we want to live in.
First published as Le temps des algorithmes by Editions Le Pommier 2020.
Title from publisher's bibliographic system (viewed on 17 Mar 2020).
Keywords: Algorithms